The revival of the Anu cult and the nocturnal fire ceremony at late Babylonian Uruk - Krul, Julia (Culture and history of the ancient Near East, 2018)
"In The Revival of the Anu Cult and the Nocturnal Fire Ceremony at Late Babylonian Uruk, Julia Krul offers a comprehensive study of the rise of the sky god Anu as patron deity of Uruk in the Late Babylonian period (ca. 480-100 B.C.). She reconstructs the historical development of the Anu cult, its underlying theology, and its daily rites of worship, with a particular focus on the yearly nocturnal fire ceremony at the Anu temple, the Bit Res. Providing the first in-depth analysis of the ceremony, Julia Krul convincingly identifies it as a seasonal renewal festival with an important exorcistic component, but also as a reinforcement of local hierarchical relationships and the elite status of the Anu priesthood"--